Financial feasibility analysis of establishing a red ginger essential oil agro-industry - Nurfauziah, Isni; Nurjanah, Sarifah; Thoriq, Ahmad; Ainina, Nurul (Journal of Systems Engineering and Management, 2023)
Red ginger is a commodity that is capable of producing antioxidants which can also be processed into various kinds of products, one of which is red ginger essential oil. Red ginger oil production business has good prospects, with the reason that not many producers produce red ginger essential oil, the possibility of profit is quite large, and the nature of red ginger which is an antioxidant commodity increases the opportunity for red ginger essential oil to be needed in the community. The purpose of this research is to analyze the financial feasibility of establishing a red ginger essential oil agro-industry. The method used in this research is descriptive quantitative. Data processing carried out in this study uses three working capital scenarios, namely 100% personal capital, conventional bank loans with a ratio of 50:50, and Islamic bank loans, with the NPV feasibility parameter (Net Present Value), IRR (Internal Rate of Return), BCR (Benefit Cost Ratio), and PBP (Payback Period). The results of this study indicate that all scenarios have NPV values of IDR 46.333.705.188, IDR 44.872.421.424, and IDR 46.386.954.684 respectively, IRR values of 14,29%, 13,37%, and 13,77%, BCR were 2,06, 1.92 and 1.98, and PBP values were 8 months, 8 months and 8 months. These values indicate that the establishment of this essential oil agro-industry is feasible, with the best planning falling into a scenario with the entire working capital of the founder. However, if personal capital financing has problems, borrowing through Islamic banks is the methodnet profit sharing can be an alternative.